Sensitive Leptospira DNA detection using tapered optical fiber sensor coated with carbon quantum dots - Zainuddin, Nurul Hida (2019)
This thesis presents a study of Leptospira DNA detection via tapered single mode optical fiber (SMF). The tapered region of the optical fiber was functionalised by sensing layer so that any reactions with the sample of interest would change the sensing layer properties. The specific capture probe DNA was designed to hybridise with complementary target Leptospira DNA. The specificity was detected using non-complementary target DNA while the cross-reactivity was tested with genomic Leptospira DNA. The urge to develop this sensor is purposedly to fulfill the demand in medical technology that is against leptospirosis. Leptospirosis is a disease infected from Leptospira bacteria to human. The issue arises when leptospirosis has vague clinical signs and likely to be under-diagnosed which may lead to human fatal. Moreover, the current diagnostic available is inadequate to get rapid, accurate, and easy detection. Therefore, alternative detection of Leptospira bacteria that addresses these issues is highly important in medical diagnostic for leptospirosis. In this PhD project, a novel and sensitive tapered optical biosensor was developed for detection of Leptospira DNA. The operation of tapered optical fiber technology platform was based on the change in optical properties upon hybridization of the desired single strand DNA (ssDNA) to capture probe DNA. It involved a modification of SMF by tapering process to enhance evanescent field interaction with the surrounding. Apart from testing the bare tapered fiber, the modified optical fiber was also coated with carbon quantum dot (CQDs) to improve the DNA sensing capability. Following that, the tapered region of the optical fiber was functionalised by incubating process using simple and commercialized chemicals to link with the probe DNA. Two types of 16s ribosomal RNA gene (rrs) probe DNA (non-terminated and amine-terminated) This thesis presents a study of Leptospira DNA detection via tapered single mode optical fiber (SMF). The tapered region of the optical fiber was functionalised by sensing layer so that any reactions with the sample of interest would change the sensing layer properties. The specific capture probe DNA was designed to hybridise with complementary target Leptospira DNA. The specificity was detected using non-complementary target DNA while the cross-reactivity was tested with genomic Leptospira DNA. The urge to develop this sensor is purposedly to fulfill the demand in medical technology that is against leptospirosis. Leptospirosis is a disease infected from Leptospira bacteria to human. The issue arises when leptospirosis has vague clinical signs and likely to be under-diagnosed which may lead to human fatal. Moreover, the current diagnostic available is inadequate to get rapid, accurate, and easy detection. Therefore, alternative detection of Leptospira bacteria that addresses these issues is highly important in medical diagnostic for leptospirosis. In this PhD project, a novel and sensitive tapered optical biosensor was developed for detection of Leptospira DNA. The operation of tapered optical fiber technology platform was based on the change in optical properties upon hybridization of the desired single strand DNA (ssDNA) to capture probe DNA. It involved a modification of SMF by tapering process to enhance evanescent field interaction with the surrounding. Apart from testing the bare tapered fiber, the modified optical fiber was also coated with carbon quantum dot (CQDs) to improve the DNA sensing capability. Following that, the tapered region of the optical fiber was functionalised by incubating process using simple and commercialized chemicals to link with the probe DNA. Two types of 16s ribosomal RNA gene (rrs) probe DNA (non-terminated and amine-terminated) were used in this study. Detection was achieved with the occurrence of hybridisation between the probe DNA and its complementary DNA, in this case, target ssDNA. The surface morphologies of functionalised bare tapered optical fiber were studied using scanning electron microscopy (SEM) while Field Emission Scanning Electron Microscope (FESEM) was used for asprepared and annealed CQDs coated. Other characterisations conducted were atomic force microscopy (AFM), energy dispersive spectroscopy (EDS) and Raman spectroscopy. Similar characterisations were also performed on Leptospira DNA hybridisation. The transmission spectrum of the DNA-based optical fiber sensor was measured in the 1500 – 1600 nm wavelength range. It was discovered that hybridisation shifts of the wavelength for all testing were linearly proportional with the increase of the complementary DNA concentrations from 0.1 nM to 1.0 nM. The sensitivities of the functionalised bare tapered optical fiber detection using non-terminated and amine-terminated probe towards DNA were measured to be 1.2876 nm/nM and 1.7301 nm/nM, respectively. Meanwhile the signal response enhancement was established using tapered optical fiber coated with CQDs. The sensitivities obtained for as-prepared and annealed CQDs coated on tapered optical fiber for non-terminated probe DNA were 1.8295 nm/nM and 2.3211 nm/nM, respectively while for amineterminated probe were 2.104 nm/nM and 2.7621 nm/nM, respectively. The findings indicate the sensor high specificity when minimal shift was detected for non-complementary DNA using all functionalised bare or CQDs coated on tapered optical fiber. This novel sensor was also able to distinguish between genomic DNA of Leptospira serovars against Clostridium difficile as the control sample. In conclusion, the work presented in this thesis lays the development of a sensitive and effective biosensor for Leptospira bacterial detection based on their specific DNA sequence analysis. This groundwork of tapered optical biosensor is highly potential for real time zoonotic disease diagnosis with in situ measurement capability at very low (femtomolar) target concentrations.